Pre-school libraries ; a survey of services on reading promotion and literature awareness of children - Tabique, Vita Angeli Philein V. (School of Library and Information Studies, University of the Philippines Diliman, 2006)
The education of young Filipino children has been given much importance over the years. This can be seen in the growth of schools offering preschool levels. Equally apparent is the proliferation of independent or exclusive preschools that are not affiliated to larger educational institutions.